1992
DOI: 10.1007/bf00051357
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of stomach cancer and its relation to diet, cigarettes, and alcohol consumption in Saitama Prefecture, Japan

Abstract: A case-control study of stomach cancer in relation to dietary, smoking, and drinking habits was undertaken in Saitama Prefecture, Japan. The study was based on 294 cases of newly diagnosed adenocarcinoma of the stomach at a single institution, 294 general population controls (matched by sex, age, and administrative division), and 202 hospital controls. Dietary habits were investigated based on the intake of 12 separate foods and 12 food groups in a food frequency questionnaire, together with individual food pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
1
4

Year Published

1997
1997
2004
2004

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 23 publications
5
81
1
4
Order By: Relevance
“…Moreover, many epidemiological studies showed that salt or salted food intake increased the risk of gastric cancer (Kono and Hirohata, 1996), including those conducted among Japanese (Tajima and Tominaga, 1985;Hoshiyama and Sasaba, 1992;Tsugane et al, 1992b). Intragastric highsalt concentration destroys the mucosal barrier, and leads to inflammation and damage such as diffuse erosion and degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many epidemiological studies showed that salt or salted food intake increased the risk of gastric cancer (Kono and Hirohata, 1996), including those conducted among Japanese (Tajima and Tominaga, 1985;Hoshiyama and Sasaba, 1992;Tsugane et al, 1992b). Intragastric highsalt concentration destroys the mucosal barrier, and leads to inflammation and damage such as diffuse erosion and degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, in the majority of case-control studies, positive associations were observed for (total) salt or sodium intake [2,3,33,34], consumption of salted fish, salted meat, pickles and soup [5,7,16,[34][35][36][37][38][39][40], adding salt to food at dinner [5,9,41], preference of salty foods [4,5,11,40,42]. The relative risks reported ranged from 1.5 to 6.7 for various measures of salt intake [14].…”
Section: Discussionmentioning
confidence: 99%
“…These variables were assessed by the baseline questionnaire and were selected as covariates because they were known or suspected to modify the risk of stomach cancer. [3][4][5][6][7] In the present analysis, salty-food preference was categorized into 3 levels (dislike, neutral, like). Frequency of food and green tea consumption was categorized into 5 levels (everyday, 3-4 times a week, 1-2 times a week, 1-2 times a month and seldom).…”
Section: Discussionmentioning
confidence: 99%
“…1,2 A number of environmental factors are now known to be related to the development of the disease. [3][4][5][6][7] At the same time, familial aggregation of this neoplasm has long been observed. 8 Many studies so far have revealed that presence of a family history of stomach cancer is associated with increased risk of developing the disease in both men and women.…”
mentioning
confidence: 99%